2020
DOI: 10.3390/plants9081003
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of N Form and P Concentration on Growth and Tissue Composition of Hybrid Napier Grass (Pennisetum purpureum × Pennisetum americanum)

Abstract: This study aimed to assess effect of nitrogen (N) form and phosphorus (P) level on the growth and mineral composition of hybrid Napier grass. Experimental plants were grown with different N forms (NO3−, NH4NO3, and NH4+; 500 µM) and P concentrations (100 and 500 µM) under greenhouse conditions for 42 days. Growth rate, morphology, pigments, and mineral nutrients in the plant tissue were analysed. At the low P concentration, the better growth was found in the plants supplied with NH4+ (relative growth rate (RGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…This outcome is consistent with research done by Kekere et al (2020) on Solanum lycopersicum, Solanum melongena, and Capsicum annuum. It also accords with studies on Pennisetum purpureum, Sinapis alba, Helianthus annus, and Medicago sativa, where plant growth and development were aided by abattoir wastewater (Pakwan et al, 2020). Similar to this, Castrol et al (2011) revealed that AWW irrigation influenced plant growth and development in a favourable manner.…”
Section: Effect Of Abattoir Wastewater On Growth Parameters Of Solanu...supporting
confidence: 84%
“…This outcome is consistent with research done by Kekere et al (2020) on Solanum lycopersicum, Solanum melongena, and Capsicum annuum. It also accords with studies on Pennisetum purpureum, Sinapis alba, Helianthus annus, and Medicago sativa, where plant growth and development were aided by abattoir wastewater (Pakwan et al, 2020). Similar to this, Castrol et al (2011) revealed that AWW irrigation influenced plant growth and development in a favourable manner.…”
Section: Effect Of Abattoir Wastewater On Growth Parameters Of Solanu...supporting
confidence: 84%